A spatial and fleet disaggregated approach to calculating the NOX emissions inventory for non-road mobile machinery in London. (December 2021) - Desouza, C.D.; Marsh, D.J.; Beevers, S.D.; Molden, N.; Green, D.C.
Abstract: The latest London atmospheric emissions inventory (2016), which is calculated using fuel consumption and construction employment, estimates that, the construction sector contributes 34% of the total PM10 emissions (the largest source), and 7% of the total NOX emissions (5 th largest source). These contribute significantly to NO2 and PM2.5 pollution problems in London, which is a major concern for public health. Real-world emission factors from tail-pipe measurements were coupled to a register for construction machinery, to develop a novel 'spatial and fleet disaggregated' emissions inventory for the construction sector in London. This method estimated 1, 294 tonnes of NOX in 2018 and 1, 578 tonnes of NOX in 2019 from non-road mobile machinery in the construction sector, approximately 55% and 45% lower for 2018 and 2019 respectively, than the current (2016) London atmospheric emissions inventory (2850 tonnes). However, compared to the current London atmospheric emissions inventory, the new NOX emissions are higher in central London, under-estimating the importance of this source in central London. The fleet-disaggregated emissions inventory enables potential policy to be developed by focusing on high-emitters registered on the London database. As a demonstration, two emission abatement scenarios were modelled – first: by retrofitting older generators with a SCR-DPF system, a potential 53% reduction in overall NOX emissions was predicted from all NRMM; and second: by accelerating the excavator fleet-turnover – a more modest 2-tonne reduction in overall NOX emissions was predicted from all NRMM in London. Graphical abstract: Image 1 Highlights: Real-world emission factors from tail-pipe measurements were coupled to a register for construction machinery, to develop a novel method to calculating the NRMM emissions inventory in London 1294 tonnes of NOX in 2018 from NRMM in the construction sector, approximately 55% lower than 2016 LAEI This novel method enables potential policy to be developed by focusing on high-emitters registered on the London database.